Tahap Persiapan Penelitian Tindakan Berbasis Partisipasi: Asesmen Awal Isu Kesehatan Mental di Sekolah - Bertrand, Jonathan; Novianty, Anita (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2023)
The goal of this study to capture initial assessment to understand students and schools’ characteristics in general to adapt the module according to the context of students and their schools. The participants consisted of 7 teachers and 21 students from 3 private high schools which selected by purposive sampling. The design of this study employed participatory action research. This study described the initial assessment as the first stage of design. Focus group discussion and observation were applied to collect data. Thematic analysis was used to analyze data. The results showed schools had a very tight schedules in their curricula which impacted to the lack of attention to mental health states of students. It is implied the urgency of further facilitation to students to understand their mental health states, as well as the ability to seek help.